Dapagliflozin reduces systemic inflammation in patients with type 2 diabetes without known heart failure - Dennis D. Wang; Anna V. Naumova; Daniel Isquith; Jamie Sapp; Kim A. Huynh; Isabella Tucker; Niranjan Balu; Anna Voronyuk; Baocheng Chu; Karen Ordovas; Charles Maynard; Rong Tian; et al. (Cardiovascular Diabetology, 2024)
Abstract Objective Sodium glucose cotransporter 2 (SGLT2) inhibitors significantly improve cardiovascular outcomes in diabetic patients; however, the mechanism is unclear. We hypothesized that dapagliflozin improves cardiac outcomes via beneficial effects on systemic and cardiac inflammation and cardiac fibrosis. Research and design methods This randomized placebo-controlled clinical trial enrolled 62 adult patients (mean age 62, 17% female) with type 2 diabetes (T2D) without known heart failure. Subjects were randomized to 12 months of daily 10 mg dapagliflozin or placebo. For all patients, blood/plasma samples and cardiac magnetic resonance imaging (CMRI) were obtained at time of randomization and at the end of 12 months. Systemic inflammation was assessed by plasma IL-1B, TNFα, IL-6 and ketone levels and PBMC mitochondrial respiration, an emerging marker of sterile inflammation. Global myocardial strain was assessed by feature tracking; cardiac fibrosis was assessed by T1 mapping to calculate extracellular volume fraction (ECV); and cardiac tissue inflammation was assessed by T2 mapping. Results Between the baseline and 12-month time point, plasma IL-1B was reduced (− 1.8 pg/mL, P = 0.003) while ketones were increased (0.26 mM, P = 0.0001) in patients randomized to dapagliflozin. PBMC maximal oxygen consumption rate (OCR) decreased over the 12-month period in the placebo group but did not change in patients receiving dapagliflozin (− 158.9 pmole/min/106 cells, P = 0.0497 vs. − 5.2 pmole/min/106 cells, P = 0.41), a finding consistent with an anti-inflammatory effect of SGLT2i. Global myocardial strain, ECV and T2 relaxation time did not change in both study groups. Clinical Trial.gov Registration NCT03782259.